COVID-19 and sustainable development goals (SDGs): An appraisal of the emanating effects in Nigeria - Fisayo Fagbemi (African Governance and Development Institute (AGDI), 2021)
The paper appraised the emanating effect of COVID-19 on sustainable development goals (SDGs) in Nigeria through the systematic illustration of the prevailing incidents. It was affirmed that the preoccupation with the COVID-19 cases caused many other critical socioeconomic issues (like education, infrastructure development, and employment) to suffer a state of negligence or be overlooked. Like other developing countries, Nigeria could become poorer, given the increased unemployment rate and the anticipated difficulty in servicing debt resulting from the COVID-19 outbreak. Hence, festering challenges including poverty, limited access to health care, low education quality, poor road networks among others, could be further entrenched. These incidents could be detrimental to sustainable development goals (SDGs) 2030 agenda. The current crisis, therefore, poses a threat to Nigeria's development prospects, as it may take more time to recover, especially in the post-COVID-19 era. Thus, it is critical to recognize the significance of securing strong institutional regulatory setup and resources (including financial and material resources) needed to facilitate sustainable change in the economy.
Keywords: 330; COVID-19; economic crisis; sustainable development goals (SDGs); Nigeria